STANDARDIZATION OF SPECIFIC PARAMETERS OF CITREH (Cymbopogon citratus) ETHANOL EXTRACT AS A NATURAL ANTIOXIDANT - Titi Agni Hutahaen; Nawafila Februyani (LPSDI Bina Patria, 2023)
Antioxidants can prevent damage caused by excessive exposure to free radicals such as exposure to ultraviolet light and air pollution. Lemongrass is known to contain flavonoids, saponins, phenols, alkaloids, steroids which are compounds that have antioxidant activity. The antioxidant content of lemongrass fruit allows this fruit to be developed as cosmetic, herbal, insect repellent, and essential oil products. Standardization of components of secondary metabolic compounds is very important, this will be used as a guide or parameter in determining compounds and raw materials later in product development. In order to obtain a standardized product. The development of citronella extract has started in recent years, one of which is product development, namely insect repellent and essential oil. Parameters for determining standardized citronella raw materials will produce standard compounds in relation to being active ingredients in a product. Standardization of extract parameters will play an important role in determining the final result or influencing the antioxidant activity of the product to be produced. The specific parameters that will be carried out later will be more on the phytochemical test for levels of secondary metabolites from the kitchen citronella and will increase the selling value of the citronella. The IC50 value of the ethanol extract of citronella is 71.96 ppm or has a Strong category. Phytochemical Test Results Lemongrass contains alkaloids, flavonoids, phenolics, tannins, saponins